Will the energy industry drain the water used for agricultural irrigation in the Yellow River basin?. Issue 1 (2nd January 2017) - Xiang, Xiaozhi; Svensson, Jesper; Jia, Shaofeng
Abstract: This article employs the case of the Yellow River basin to advance understanding of the water–energy–food nexus by demonstrating how the country's energy and agriculture sectors are competing for limited water supplies and by quantifying the future water demands in the two sectors. The results show that in 2030 the water demands for food and energy are likely to increase by less than 4 km 3 and 1 km 3, respectively, in the Yellow River basin. The analysis suggests that agricultural water savings and inter-basin water transfers are the main ways to ensure sufficient water flows through the basin to fulfil demand for both sectors while preserving the natural ecosystems.